Correlation of silent brain infarcts and leukoaraiosis in middle-aged ischemic stroke patients: a retrospective study - Abdulsalam, Mohammad Fathi; Shaheen, Nour; Shaheen, Ahmed; Alabdallat, Yasmeen Jamal; Ramadan, Abdelraouf; Meshref, Mostafa; Mansour, Fathy Mahmoud; Abed, Elsayed; Fayed, Abdel-Ghaffar I.; Zaki, Mohamed Ahmed; El-Adawy, Ahmad F.; Flouty, Oliver; et al. (Frontiers in Neurology, 2024)
Background: Cerebrovascular diseases of the brain are usually defined by transient ‎ischemic attacks and strokes. However, they can also cause brain injuries without ‎neurological events. Silent brain infarcts (SBI) and leukoaraiosis are symptoms of both ‎vascular and neurological abnormalities. This study aims to investigate the association ‎between SBI, leukoaraiosis, and middle-aged patients with ischemic stroke. ‎ Methods: A single-centre retrospective study of 50 middle-aged, ischemic stroke ‎patients were studied from November 2022 and May 2023. The patients were divided ‎into two groups based on the presence or absence of leukoaraiosis. History taking, ‎physical examination, brain CT scan, and MRI were all part of the diagnostic process. ‎Metabolic syndrome (MetS ) was also assessed through various factors. The statistical ‎analysis included descriptive statistics, logistic regression analysis, and chi-square test. ‎ Results: Out of the cohort comprising 50 patients, characterized by a mean age of ‎‎52.26 years (SD 5.29), 32 were male, constituting 64% of the sample. Among these ‎patients, 26 individuals exhibited leukoaraiosis, with 17 of them (65.4%) also presenting ‎with SBI. Moreover, within this cohort, 22 patients were diagnosed with MetS, ‎representing 84.6% of those affected. The Multivariate logistic regression analysis ‎showed a strong and independent association between Leukoaraiosis and SBI. ‎Individuals with Leukoaraiosis were nearly five times more likely to have SBI compared ‎to those without Leukoaraiosis. ‎ Conclusions: The study highlights leukoaraiosis as a significant risk factor for SBI, ‎alongside MetS. Advanced imaging techniques have facilitated their detection, revealing ‎a higher prevalence among stroke patients, particularly associated with age and ‎hypertension. Further research is needed to fully understand their complex relationship ‎and develop better management strategies for cerebrovascular diseases, ultimately ‎improving patient outcomes.‎